PENGARUH PEMBERDAYAAN KARYAWAN DAN ORGANISASI PEMBELAJARAN TERHADAP KOMITMEN ORGANISASI DALAM MENINGKATKAN ORGANIZATIONAL CITIZENSHIP BEHAVIOR (Studi Kasus PT SUCOFINDO (Persero) Kantor Cabang Semarang) - Ridha Maulina; Endang Sulistyani; Suharmanto Suharmanto (Politeknik Negeri Semarang, 2018)
This research aims to determinethe effect of employee empowerment onorganizational commitment, knowing the influence of learning organization on organizational commitment, and determine the influence of organizational commitment on organizational citizenship behavior (OCB). The sample consisted 120 respondents. The data was collected using a questionnaire, interviews and literature. After that data analysis techniques processed using SEM with AMOS program 22.0. Result of this study indicates that employee empowerment, and learning organization has a significant and positive impact on organizational commitment, as well as organizational commitment effect significant and positive on organizational citizenship behavior (OCB). These findings provide useful suggestion for the management in PT. SUCOFINDO (Persero) Semarang Branch Office to learn developing organizational commitment and organizational citizenship behavior by adopt implementation of specific guidelines that could ultimately lead organizational competitiveness.